Some Aspects of Argumentative Theory of Rhetoric in Islamic Religious Discourse - Rafiq Mohammad Shawani; Yousif Noori Muhammadamin (Zanco Journal of Humanity Sciences)
This research, entitled (Some Aspects of the Argumentative Theory of Rhetoric in Islamic Religious discourse), discusses the Argumentative Theory of Rhetoric in religious discourse. According to this theory, argument consists of a set of techniques, which are used within the discourse to convince the audience for the directive messages to him/her or to increase the level of his/her convincing. In addition to the introduction and conclusion, the research consists of two parts, the first part consists of two sections. The first section discusses definition, concept, subject, function, objective, aspect and features of argument according to this theory. In the second section, concept of discourse and Islamic religion discourse have explained. The second part has discussed the use of all the three main ways of using argument in religious speech. The first way includes argument types by communication such as semi-logical arguments and arguments which are based on reality as well as arguments which base reality. The second way is to create arguments by separating the concepts from each other, and the third way is to create arguments by using values. Finally, the conclusion and abstract of the research, in both Arabic and English, have explained.